FEATURES OF MICROFLORA FORMATION IN YOUNG CHILDREN AND ITS CORRECTION WITH PROBIOTICS - L.I. Kafarskaya; M.L. Shunikova; B.A. Efimov; A.N. Shkoporov; Yu.M. Golubtsova; Yu.A. Sigova (Педиатрическая фармакология, 2011)
The article covers the problem of current importance concerning the child bowel biocenosis species composition in different age periods of a child life. Numerous studies indicate that the species composition of the intestinal microflora is being formed during a long time. It is different in children depending on their age and is characterized by the high levels of not only the anaerobic microflora, but also allochthonous bacteria. It is known that the maturation of the immune system occurs during the newborn contacts with the bacterial and food agents, including bacteria of the normal intestinal flora, have immunomodulatory properties. Considering literature data and results of their own research, the authors provide recommendations for the optimizing use of probiotic preparations.Key words: intestinal microflora, probiotic strains, children.